Influence of Strategic Interrelationships and Decision-Making in Chilean Port Networks on Their Degree of Sustainability - Palominos-Villavicencio, F (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
An extensive literary review is carried out to determine the strategic and business advantages, and difficulties that non-smart ports must face to develop sustainability. Based on a two-port case study, the strategic text of the corporate missions of port administrators and operators is analyzed and classified in order to understand to what extend economic, social and environmental aspects are fulfilled. A conceptual model is designed for an information system based on indicators that can determine the state or degree of sustainability in the critical operational activities of the ports studied. A system is proposed that is based on a data warehouse core and a multidimensional database, which can be implemented in the Relational On-Line Analytical Processing (ROLAP) mode, allowing taking advantage of the good characteristics of relational databases without losing the On-Line Analytical Processing (OLAP) approach. A discussion of the strategic feasibility of implementing this conceptual model of case study monitoring and its long-term benefits is delivered. The conclusions state that the development of this green technology requires cultural changes, public policy initiatives and the incorporation of new actors. In addition, more research is needed in this area to identify other relevant sustainable variables. © 2021 by the authors.